Identifying and prioritizing evidence needs in self-care interventions for sexual and reproductive health - Gilda Sedgh; Annik Sorhaindo (Frontiers Media S.A., 2023)
BackgroundSelf-care as an extension of health care systems can increase access to care. The development of programs and generation of evidence to support self-care in sexual and reproductive health (SRH) is a relatively nascent field. We undertook a study to identify and prioritize evidence gaps for SRH self-care.MethodsWe used the CHNRI methodology and administered two online surveys to stakeholders affiliated with major self-care networks. The first survey was used to identify evidence gaps, and the second to prioritize them using predetermined criteria.ResultsWe received 51 responses to the first survey and 36 responses to the second. Many evidence gaps focused on awareness of and demand for self-care options and best mechanisms for supporting users of self-care with information, counseling and linkages to care.ConclusionA priority area of work ahead should be determining which aspects of the learning agenda reflect gaps in evidence and which reflect a need to effectively synthesize and disseminate existing evidence.